Statistics for managers using Microsoft Excel - Levine, David M. (Prentice Hall, 1999)
Introduction and data collection. Using Microsoft Excel for statistical analysis. Presenting data in tables and charts. Summarizing and describing numerical data. Basic probability and discrete probability distributions. Decision making. The normal distribution and sampling distributions. Confidence interval estimation...